Efficacy and workload analysis of a fixed vertical couch position technique and a fixed‐action–level protocol in whole‐breast radiotherapy - Petillion, Saskia (J Appl Clin Med Phys, 2015)
Quantification of the setup errors is vital to define appropriate setup margins preventing geographical misses. The no‐action–level (NAL) correction protocol reduces the systematic setup errors and, hence, the setup margins. The manual entry of the setup corrections in the record‐and‐verify software, however, increases the susceptibility of the NAL protocol to human errors. Moreover, the impact of the skin mobility on the anteroposterior patient setup reproducibility in whole‐breast radiotherapy (WBRT) is unknown. In this study, we therefore investigated the potential of fixed vertical couch position‐based patient setup in WBRT. The possibility to introduce a threshold for correction of the systematic setup errors was also explored. We measured the anteroposterior, mediolateral, and superior–inferior setup errors during fractions 1–12 and weekly thereafter with tangential angled single modality paired imaging. These setup data were used to simulate the residual setup errors of the NAL protocol, the fixed vertical couch position protocol, and the fixed‐action–level protocol with different correction thresholds. Population statistics of the setup errors of 20 breast cancer patients and 20 breast cancer patients with additional regional lymph node (LN) irradiation were calculated to determine the setup margins of each off‐line correction protocol. Our data showed the potential of the fixed vertical couch position protocol to restrict the systematic and random anteroposterior residual setup errors to 1.8 mm and 2.2 mm, respectively. Compared to the NAL protocol, a correction threshold of 2.5 mm reduced the frequency of mediolateral and superior–inferior setup corrections with 40% and 63%, respectively. The implementation of the correction threshold did not deteriorate the accuracy of the off‐line setup correction compared to the NAL protocol. The combination of the fixed vertical couch position protocol, for correction of the anteroposterior setup error, and the fixed‐action–level protocol with 2.5 mm correction threshold, for correction of the mediolateral and the superior–inferior setup errors, was proved to provide adequate and comparable patient setup accuracy in WBRT and WBRT with additional LN irradiation. PACS numbers: 87.53.Kn, 87.57.‐s